Implementasi Metode Certainty Factor Untuk Mendiagnosis Penyakit Malaria - Linda Perdana Wanti; Ulfiyah, Waffa (KLIK: Kajian Ilmiah Informatika dan Komputer, 2024)
Malaria is a disease caused by the plasmodium parasite transmitted through the bite of an infected female anopheles mosquito. This disease often occurs in tropical and subtropical areas, including Indonesia. Symptoms of malaria generally appear between 10-15 days after the bite of an infected mosquito and include high fever, chills, sweating, headache, nausea, vomiting, muscle aches, and fatigue. The first identification is carried out when the patient comes to a health facility and perhaps the disease is already in a severe phase. A system that can identify malaria quickly and precisely is needed for emergencies so that patients receive early treatment, and this is one of the preventive measures to reduce casualties due to malaria. The right system built to overcome this is expert. The certainty factor (CF) method was chosen for the malaria diagnosis expert system because it handles uncertainty in decision-making. CF is a numerical value used to represent confidence or confidence in a hypothesis or conclusion based on existing evidence. The result of this research is that the level of accuracy of expert system diagnosis using the certainty factor method is 98,35% when compared with expert diagnosis. This means that the certainty factor method has been proven to be able to diagnose malaria accurately according to the symptoms experienced by the patient.